Folkestone futures: an elevated excursion. Issue 1 (2nd January 2016) - Whybrow, Nicolas
Abstract: The town of Folkestone on the south Kent coast in the UK once enjoyed a thriving identity as both seaside resort and gateway to Europe. From the 1960s onwards a gradual decline set in with the advent of mass global travel, culminating in the deathblow that was dealt by the nearby Eurotunnel's inauguration towards century's end, which signalled the end of the town's ferry link to the continental mainland. A concerted attempt has been underway for a decade now to revitalise the town using the arts, creative industries and education as the drivers of regeneration. One of the main initiatives in this endeavour was the introduction in 2008 of the Folkestone Triennial, a three-month summer event in which high-profile international artists were commissioned to produce sited artworks for the town. Focusing on the third triennial in 2014, this article analyses some of the ways in which artists have sought to engage and identify with notions suggested by its title, Lookout . In particular it will outline a curated constellation of artworks – or complex – that implicitly inscribes itself into the townscape and is characterised by installations that are sited in elevated locations, from whose respective vantage points they contemplate what the future holds for Folkestone.